Personal and Family Finance in the Marriage and Family Therapy Domain - Dorothy B Durband; Sonya L Britt; John E Grable (Journal of Financial Therapy, 2010)
The purpose of this study was to determine what changes have occurred in the past 20 years in accredited marriage and family therapy (MFT) programs in terms of student training and preparation for treating family financial concerns. MFT program directors (N = 18) and students (N = 102) responded to an emailed a web survey. Findings indicated that only two master’s degree programs, two doctoral programs, and one post-graduate program offered a personal or family finance course elective. A discussion about the implications this limited exposure to personal finance topics plays in professional training is provided.
Keywords: Personal finance; Marriage and Family Therapy